European fuel economy policy for new passenger cars: a historical comparative analysis of discourses and change factors - Takahiro Oki (International Environmental Agreements: Politics, Law and Economics, 2020)
In April 2019, the European Union (EU) revised its fuel economy policy for new passenger cars (PC). The new standard set an ambitious policy framework that featured high CO2 caps on these vehicles from 2025 and 2030 with limited flexibility for automobile industry to comply with the new standard, reflecting European decision-makers' aspirations for zero-emission mobility. Most literature on EU policy-making and interest representation has pointed out the power of automobile industry and argued that these industry actors were able to influence the stringency of actual emission standards in the timeframe of 2012 and 2020. However, this conventional view of the dominance of automobile industry does not sufficiently explain why European policy-makers were able to change their fuel economy policy so significantly in 2019. To fill this research gap in the existing literature, this research focuses on discourses and coalitions of actors who deployed these discourses throughout three legislative processes that have shaped the EU's fuel economy policy: Regulation 443/2009, Regulation 2014/333 and Regulation 2019/613. This research not only considers the interests and powers of relevant actors, which are the primary focus of much of the existing literature; but also a range of ideas and discourses that they have brought to policy discussions. Drawing on the theoretical literature of argumentative discourse analysis (ADA) and policy change, this article attempts to highlight discursive battles within key actors over the stringency of EU's fuel economy policy on PCs.
Keywords: 330; Fuel economy; Passenger cars (PC); Discourse change; Multi-level governance; European Union